The Role of Anonymous Data in Promoting Consumer Loyalty on E-commerce Platforms in Indonesia - Judijanto, Loso; Achmady, Sayed; Utama, I Wayan Karang; Effendy, Femmy; Sabila, Puji Chairu (The Eastasouth Journal of Information System and Computer Science, 2024)
This study investigates the role of anonymous data in driving consumer loyalty on e-commerce platforms in Indonesia. Employing a quantitative approach, data was collected from 60 respondents through a structured questionnaire using a Likert scale (1-5). Statistical analysis using SPSS version 25 reveals a significant positive relationship between anonymous data utilization and consumer loyalty. Anonymous data enables personalized recommendations and targeted promotions while maintaining consumer privacy, fostering trust and engagement. The study highlights the importance of ethical data practices in the Indonesian e-commerce landscape and provides actionable insights for businesses aiming to enhance customer retention. Limitations and future research directions are also discussed.